Characteristics of patients who committed suicide during hospitalization in psychiatric hospital »Vrapče« in the period 1996–2006 - Brečić, Petrana (Array, 2009)
Abstract: The aim of this study was to determine the characteristics of psychiatric inpatients who committed suicide in the Vrap~e Psychiatric Hospital with respect to clinical, ethical, and legal context. The study included all patients hospitalized in the Vrap~e Psychiatric Hospital between 1 January 1996 and 31 December 2006 who committed suicide (n=25). The suicide rate in the observed period was 32.9 per 100.000 (suicide coefficient, 50), which is similar that in general population. Based on the characteristics of hospitalized patients who committed suicide, we obtained a typical profile as follows: a middle-aged person, single, unemployed, repeatedly hospitalized, with schizophrenia and a history of suicide attempts, committing suicide using a violent method after more than three weeks of hospital treatment. If further prevention of hospital suicide will be treated as a legal rather than medical issue, the hospital atmosphere would be totalitarian rather than therapeutic. The success of psychiatric treatment is the perception of both of these aspects of suicide as well as their efficient balancing